System frequency & tie-line control (Transmission system operation)
The objective of this module is to present the causes and effects of frequency variation, and to demonstrate the actions required by the operator to control frequency and maintain the scheduled tie-line flows between neighboring control areas. Topics include interconnection of control areas, continous need to balance power demand and generation, the contribution of prime mover governors to frequency control, the contribution of AGC (Automatic Generation Control), the effects of generation/load unbalance on tie-line flows and operator actions required to restore stable conditions.